C2C Startup Model of Balinese Ceremony Ticketing System in Ubud Bali - Suryawan, I Wayan Dharma; Saraswati, Ni Wayan Sumartini; Hartono, Eddy (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 15 No 03 (2024): Vol.15, No. 3 December 2024, 2025)
Ubud is one of the tourist destinations in Bali. Ubud combines natural attractions, culture, and spiritual life harmoniously. One of the elements of cultural attraction in Ubud is the implementation of traditional and religious ceremonies that uphold ancestral customs. With this potential, Ubud can be a tourist destination supporting Balinese cultural tourism's progress. Currently, information regarding the implementation of traditional and religious ceremonies in Ubud is limited to tourists. Tourists can witness the traditional and religious ceremonies held through information from tour guides, who are ceremony organizers. The availability of a ceremony ticketing system that connects tourists with traditional village/banjar communities can directly address the problem of access to information and services for the implementation of traditional and religious ceremonies in Ubud. This study aims to develop a C2C e-commerce model that involves klian adat and tourists directly selling tickets for traditional and religious ceremonies in Singakerta Village, Ubud District. Given the limited time for system development, the RAD software development method was selected as the system development method. The user experience test's Likert scale results showed that the system's quality reached 84.13% for tourist satisfaction and 84.19% for klian adat satisfaction. This indicates that the system is at an excellent level based on the user.